Students’ Satisfaction with Academic Support Services at the University of Benin - Agbonifoh, Christopher Ihionkhan; Dania, Omoyebagbe Rosaline (NIU Journal of Social Sciences; Vol 11 No 1 (2025): NIU Journal of Social Sciences, Vol. 11 No. 1, March 2025, 2025)
The study investigated students’ satisfaction with academic support services at the University of Benin. It precisely aimed at ascertaining the level of students’ satisfaction with teaching/educational services; evaluate the level of students’ satisfaction with library services; verify the level of students’ satisfaction with security services; determine students’ contentment with administrative/and registration services; evaluate the level of students’ satisfaction with medical services; ascertain students’ satisfaction with hostel accommodation and examine students’ satisfaction with information and communication technology (ICT). The study sample comprises of three hundred and eighty-five (395) respondents drawn from undergraduate students of University of Benin with the help of Google Form. Structured questionnaire was utilised to gather the needed information and the investigative techniques employed include simple percentages, means, correlation and multiple regression. All tests were performed at the 0.05 level of statistical significance. The result showed that teaching/educational services were positive and significantly related to students’ satisfaction in the University of Benin. Security services had a positive and significant relationship with students’ satisfaction in the University; administrative and registration services was positive and significantly related to students’ satisfaction. Medical services provided by health workers significantly affect students’ satisfaction in the University. Information and communication technology (ICT) had a positive and significant relationship with students’ satisfaction. However, library and hostel accommodation services had no significant relationship with students’ satisfaction in the University of Benin. The study therefore recommends that regular satisfaction surveys should be conducted to specifically address library and accommodation services to better understand student expectations and experiences. Keywords: Expectations, Satisfaction, Service Delivery, Service Quality, Students